Matters of the Heart : History, Medicine, and Emotion. - Alberti, Fay Bound, 1971- (OUP Oxford, 2010)
The heart is the most symbolic organ of the human body. Across cultures it is seen as the site of emotions, as well as the origin of life. We feel emotions in the heart, from the heart-stopping sensation of romantic love to the crushing sensation of despair. And yet since the nineteenth century the heart has been redefined in medical terms as a pump, an organ responsible for the circulation of the blood. Emotions have been removed from the heart as an active site of influence and towards the brain. It is the brain that is the organ most commonly associated with emotion in the modern West. So w.